PECULIARITIES OF STUDENTS’ IDEA OF HEALTH AND PHYSICAL EDUCATION AT THE UNIVERSITY - Білоус, Наталія Сергіївна; Криворучко, Світлана Миколаївна; Самохін, Олексій Олексійович; Кононенко, Неллі Миколаївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article deﬁ ned the features of students understanding of health and physical education at universities. It is shown that the higher students evaluate themselves and their health, the more positive they are for physical education and the more young men care about health-conscious and conservation, the more signiﬁ cance it has for physical education. For a young person’s health is a factor that increases his self-esteem and self-worth increases chances to ﬁ nd love and depend on gender: girls compared with boys are more concerned about their health.